An Epistatic Network Describes oppA and glgB as Relevant Genes for Mycobacterium tuberculosis - Posada-Reyes, Ali-Berenice; Balderas-Martínez, Yalbi I.; Ávila-Ríos, Santiago; Vinuesa, Pablo; Fonseca-Coronado, Salvador (Frontiers in Molecular Biosciences, 2022)
Mycobacterium tuberculosis is an acid-fast bacterium that causes tuberculosis disease worldwide. The role of epistatic interactions among different loci of the M. tuberculosis genome under selective pressure may be crucial for understanding the disease and the molecular basis of antibiotic resistance acquisition. Here, we analyzed polymorphic loci interactions by applying a model-free method for epistasis detection, SpydrPick, on a pan-genome-wide alignment created from a set of 254 complete reference genomes available to date. By means of the analysis of an epistatic network created with the detected epistatic interactions, we found that glgB (α-1,4-glucan branching enzyme) and oppA (oligopeptide-binding protein) are putative targets of co-selection in M. tuberculosis, as they were associated in the network with M. tuberculosis genes related to virulence, pathogenesis, transport systems modulators of the immune response, and antibiotic resistance. In addition, our work unveiled potential pharmacological applications for genotypic antibiotic resistance inherent to mutations of glgB and oppA, as they epistatically interact with fprA and embC, two genes recently included as antibiotic-resistant genes in the catalogue of the World Health Organization. Our findings show that this approach allows the identification of relevant epistatic interactions that may lead to a better understanding of M. tuberculosis by deciphering the complex interactions of molecules involved in its metabolism, virulence, and pathogenesis, and that may be applied to different bacterial populations.